Optimization of the Androgenesis Method in the In Vitro Culture of Anteneson the Basis ofT. AestivumHybrids - Kazachenko, A.O.; Davydova, N.V.; Burlutsky, V.A.; Romanova, E.S.; Voronov, S. I. (KnE Life Sciences, 2022)
This study aimed to examine the regularities of the regenerationprocesses of haploid plants, the dependence of in vitro microspore morphogenesis in anther culture on optimization factors, and their efficiency in F1 hybrids of T. aestivumof different ecological and geographicorigin. It was found that heterosis contributed to an increased yield of haploid chlorophyll-bearing regenerants from hybrids obtained from the crossing of parental forms with different responsiveness to androclinia. Results were obtained for the complex optimization of the androgenesis method for the in vitro anther culture of T. aestivum, in order to create diploidized haploid lines (DHL) regardless of the influence of the genotype. The agroecological properties for a complex of economically useful traits were also assessed. DHLs were created that combined high yield (5.1-6.8 t / ha) with lodging resistance (straw height – 60-80 cm) and consistently high grain quality; these were characterized by increased resistance to major leaf diseases in comparison with the standard variety in the conditions of the Central Economic Region of the Non-Black Earth Zone of the Russian Federation. Keywords: spring soft wheat, androgenesis, embyroidogenesis, callusogenesis, diploidized haploids, in vitro, yield and quality